The adsorption of Ni, Cu, Zn, Cd and Pb by δ-MnO₂ and its inclusion in an equilibrium model of metal partitioning in soils - Pretorius, Patrius Julius (Department of Chemistry, 2016)
Chemical equilibrium modelling provides a mechanistic tool for the prediction of metal partitioning in soils, which is important in predicting the fate and effects of metals in soil systems. In order to set up an equilibrium model of metal partitioning in soil systems, thermodynamic data for all processes influencing metal fate in soil systems are needed. In this work, the adsorption of the metals nickel, copper, zinc, cadmium and lead by δ-MnO₂ is investigated. This was done in order to provide thermodynamic data for an important adsorption phase in soils systems. Before this work, consistent adsorption data for only one adsorption phase, hydrous ferric oxide, were available. This precluded the inclusion of manganese dioxide in equilibrium models of metal fate in soil systems. Surface complexation properties of a synthetic manganese dioxide were investigated using glass electrode potentiometry. Experimental data were interpreted according to the surface complexation model in conjunction with the diffuse double layer model of the solid/solution interface. Adsorption constants were derived using the non-linear optimization program FITEQL. The surface complexation parameters determined in this fashion were validated against results obtained from the open literature. Following this, the surface complexation parameters were included in a chemical equilibrium model of soil systems. This model was used to predict the partitioning of nickel, copper, zinc, lead and cadmium in a number of soil samples collected in The Netherlands. Contrary to results presented by other workers, it was found that a non-homogeneous surface site model was needed to explain the potentiometric data obtained for proton and metal adsorption by manganese dioxide. Best fits of alkalimetric titration data were obtained with a two-site, three surface-species model of the δ-MnO₂ surface. Site concentrations of 2.231x10⁻³ mol.g⁻¹ and 7.656x10⁻⁴ mol.g⁻¹ were obtained. Corresponding equilibrium constants for the formation of the postulated surface species are -1.27 (=XO⁻), -5.99 (=YO⁻) and 3.52 (= YOH2₂⁺). This model was successful in a qualitative manner in describing adsorption results obtained from the open literature. The prediction of metal partitioning in soil systems showed that although the inclusion of manganese dioxide in the modelled to some improvement in the agreement between observed and predicted results, other factors are present which influence metal partitioning in soils. The discrepancy between observed and predicted results furthermore showed that the processes accounted for in the equilibrium model are incomplete.